Work, Commitment to Work and Self-Identity among Women - Chappell, Lane Neena (My University, 1978)
This thesis focuses on an empirical study of commitment to work and the importance of work for self-identity among working women. In the first chapter, a Meadian conceptualization of the self is expounded from which it is hypothesized that current adult involvements will be more relevant for current adult self-identity than will early socialization experiences. This is followed by a review of the relevant occupational and sex roles literature. Some of the traditional assumptions about working women are made explicit: women have a primary commitment to their marriage and family roles and a secondary commitment to work; it is women's part-time and temporary involvement in the labour force which is largely responsible for their secondary commitment to work; commitment to work and the importance of work for self-identity are synonymous or at least highly and positively correlated with one another. These assumptions are questioned and a conceptual distinction between commitment to work and the importance of work for self-identity is made.
The data are collected using personal interviews among working women in four occupational groups: social workers; newspaper reporters; fashion models; and privates and corporals in the Forces. These groups are chosen specifically to permit a test of the differential influence of occupational prestige and the traditional sex-characterization of the occupation on both commitment to work and the importance of work for self-identity.
The data are analyzed using regression analysis for: the sample as a whole; married working women; working mothers; and each of the four occupational groups separately. The results confirm the Meadian suggestion that current adult involvements would be more influential for current adult self-identity than would early childhood experiences. The conceptual distinction between commitment to work and the importance of work for self-identity is supported empirically. These findings point to the need for further clarification between these concepts and suggest the inadequacy of current writings which assume they are synonymous.
Factors leading to an increased importance of work for self-identity do not support the traditional assumptions about working women. Rather, the actual proportion of other women which the respondent knew is associated with an increased importance of work. This is interpreted in terms of establishing work as a legitimate role for women. Marital status, or involvement in the marriage role, leads to an increased importance of work. Finally, among working mothers, outside assistance with the children leads to an increased importance of work.
Findings for commitment to work also debunk some of the common assumptions found in the literature. It is not affected by marital status, the presence of children, the number of children, or past involvement in the labour force. Like men, women increase their comndtment to work as their occupational prestige increases. However, different findings are evident when different indicators are used. The use of lesg valid but nevertheless popularly employed indicators leads to findings which support some of the traditional assumptions. The selection of indicators is then discussed as a possible reason for some of the contradictory findings in the literature.
Keywords: Sociology; Sociology